Targeting M-MDSCs enhances the therapeutic effect of BNCT in the 4-NQO-induced murine head and neck squamous cell carcinoma model - Chang, Chun-Hsiang; Chen, Chi-Jui; Yu, Ching-Fang; Tsai, Hui-Yu; Chen, Fang-Hsin; Chiang, Chi-Shiun (Frontiers in Oncology, 2023)
Purpose: Malignant head and neck squamous cell carcinoma (HNSCC) is characterized by a poor prognosis and resistance to conventional radiotherapy. Infiltrating myeloid-derived suppressive cells (MDSCs) is prominent in HNSCC and is linked to immune suppression and tumor aggressiveness. This study aimed to investigate the impact of boron neutron capture therapy (BNCT) on the MDSCs in the tumor microenvironment and peripheral blood and to explore the potential for MDSCs depletion combined with BNCT to reactivate antitumor immunity.Methods and materials: Carcinogen, 4-NQO, -induced oral tumors were irradiated with a total physical dose of 2 Gy BNCT in Tsing Hua Open Reactor (THOR). Flow cytometry and immunohistochemistry accessed the dynamics of peripheral MDSCs and infiltrated MDSCs within the tumor microenvironment. Mice were injected with an inhibitor of CSF-1 receptor (CSF-1R), PLX3397, to determine whether modulating M-MDSCs could affect mice survival after BNCT.Results: Peripheral CD11b + Ly6C high Ly6G -monocytic-MDSCs (M-MDSCs), but not CD11b + Ly6C lo Ly6G high polymorphonuclear-MDSCs (PMN-MDSCs), increased as tumor progression. After BNCT treatment, there were temporarily decreased and persistent increases of M-MDSCs thereafter, either in peripheral blood or in tumors. The administration of PLX-3397 hindered BNCTcaused M-MDSCs infiltration, prolonged mice survival, and activated tumor immunity by decreasing tumor-associated macrophages (TAMs) and increasing CD8 + T cells.Conclusion: M-MDSCs were recruited into 4-NQO-induced tumors after BNCT, and their number was also increased in peripheral blood. Assessment of M-MDSCs levels in peripheral blood could be an 2 This is a provisional file, not the final typeset article index to determine the optimal intervention window. Their temporal alteration suggests an association with tumor recurrence after BNCT, making M-MDSCs a potential intervention target. Our preliminary results showed that PLX-3397 had strong M-MDSCs, TAMs, and TIL (tumor-infiltrating lymphocyte) modulating effects that could synergize tumor control when combined with BNCT.